2022
DOI: 10.3390/insects13040326
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the Black Soldier Fly Hermetia illucens (Diptera: Stratiomyidae) on Organic-Waste Residues and Its Application as Supplementary Diet for Nile Tilapia Oreochromis niloticus (Perciformes: Cichlidae)

Abstract: The black soldier fly, Hermetia illucens (BSF, Diptera: Stratiomyidae) is an insect with high protein value and a potential feed agent for animals aimed for human consumption. The growth parameters of BSF larvae reared on four substrates—restaurant-waste, fruit-waste, fish-waste, and commercial tilapia food—for 41 days before processing for inclusion into Oreochromis niloticus (Perciformes: Cichlidae, Nile tilapia) commercial fry diets at 30% (70:30) were determined. On fly larvae, the food substrate based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 68 publications
2
4
0
Order By: Relevance
“…The longer development time from larva to pre-pupa corroborates the work of Pérez-Pacheco et al (2022), who demonstrated that the prolongation of the period from larva to pre-pupa tends to TA B L E 5 Growth and weight (mean ± standard deviation) of Hermetia illucens bred on different residues.…”
Section: Discussionsupporting
confidence: 83%
“…The longer development time from larva to pre-pupa corroborates the work of Pérez-Pacheco et al (2022), who demonstrated that the prolongation of the period from larva to pre-pupa tends to TA B L E 5 Growth and weight (mean ± standard deviation) of Hermetia illucens bred on different residues.…”
Section: Discussionsupporting
confidence: 83%
“…Media that has good quality and quantity has a good impact on the nutritional value of H. illucens produced, as well as accelerates its growth and development. Feed formulation affects larvae's survival, developmental level, and yield (Pacheco et al 2022).…”
Section: Larvae Survival Ratementioning
confidence: 99%
“…Products based on BSF larvae (BSFL) are considered highly valuable and digestible ingredients for aquaculture [ 14 , 15 , 16 , 17 ], poultry [ 18 , 19 ], and pig [ 20 , 21 ] feeding. However, variation in nutritional profiles of BSFL may have important consequences on their feeding values [ 3 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the extent to which these effects may be attributed to different diets used for BSFL fattening or genetic differences between BSF strains remained unclear. Numerous studies rearing BSFL on different diets evidence that nutrition strongly affects commercially relevant life-history traits (e.g., [ 17 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]). Performance on seemingly comparable diets across different studies nevertheless documents notable variation [ 5 , 6 , 33 ].…”
Section: Introductionmentioning
confidence: 99%